PEMANFAATAN JAGUNG DAN LIMBAH JANGGEL UNTUK MENINGKATKAN POTENSI EKONOMI BAGI PEMUDA IPNU DAN IPPNU DESA CANGAK KABUPATEN PEMALANG - Najah, Syafinatunnajah; Nugroho, Bakti Adi; Nazilah, Rohmatun; Sunyoto, Sunyoto; Novanta, Nabella Maharani; Fauzatinnisa, Amirah; Ulum, Diah Ariibatul; Lathiif, Abdul; Setyaningrum, Novi Ayu; Jannah, Azzukhrufia; Ratnawati, Ratnawati; Agustina, Sri Mumaeni; Aprilia, Rizky Wulan; Puspitasari, Dewi (ABIDUMASY, 2025)
Cangak village is wrong one corn producing village in the Regency Pemalang. Corn can be processed into several one of the processed products is plethok corn. Not only corn that can be processed but corn waste can also be processed into briquettes. Briquettes from corn is a renewable energy alternative. Which environmentally friendly and potential replace fossil fuels. The method that used in carrying out community service includes an approach through discussion, socialization and training, and practice. Results of activities the dedication that is carried out shows that there is an increased understanding regarding transfers technology on IPNU and IPPNU youth corn made into processed snacks and corn kernels can be made into briquettes beneficial for local community MSMEs